2020
DOI: 10.31729/jnma.4806
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Stay Duration of Patients in Emergency Department of A Tertiary Care Hospital in Nepal: A Descriptive Cross-sectional Study

Abstract: Introduction: Emergency department of a hospital is responsible for providing medical and surgical care to patients arriving at the hospital in need of immediate care. Emergency department is not staffed or equipped to provide prolonged care. Duration of stay in the Emergency department directly affects the quality of patient care. Longer length of stay is associated with Emergency department overcrowding, decline in patient care, increased mortality and decreased patients satisfaction. The main aim of this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…Patients with grades 1-3 need to be admitted to the resuscitation area for emergency treatment. Resuscitation area LOS was defined as the time between recorded arrival and recorded off in the resuscitation area [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Patients with grades 1-3 need to be admitted to the resuscitation area for emergency treatment. Resuscitation area LOS was defined as the time between recorded arrival and recorded off in the resuscitation area [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…A study from Nepal also revealed an association between longer lengths of stay and ED high crowding, poor patient care, and decreased levels of patient satisfaction. 26 …”
Section: Discussionmentioning
confidence: 99%
“…It must be accessible 24 h a day, and immediacy is crucial for the quality of ED care [2][3][4]. It has become increasingly important in the healthcare delivery system, and it is now the major point of entry for inpatient admissions, discharges, and referrals [5,6]. Longer pediatric ED stays are a global problem with variable prevalence rates, such as 31.3% in Guangzhou, China, 25.7% in north Taiwan, and 16.4% in Calabar, Nigeria [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Due to an increased risk of hospital-acquired infections, morbidity, and death, as well as reduced patient satisfaction, length of stay (LOS) is associated to lower care quality, as well as parents' socioeconomic concerns, hospital occupancy rates, more significant healthcare resource limits, and patient safety [6,[12][13][14]. Several studies have found that remaining in the emergency department for an extended period of time increases death rates by 15-30% and reflects poor hospital performance.…”
Section: Introductionmentioning
confidence: 99%